Pelatihan dan Pendampingan Online dalam Penulisan Penelitian Tindakan dan Karya Tulis Imiah Bagi Guru - Kadek Suranata (Indonesian Institute For Counseling, Education and Therapy, 2020)
This community service program is a online training and assistance in writing action research and scientific articles for teachers which aims to increase motivation and ability to write action research and scientific articles for teachers in Bali Province. The combination of the synchronize method through the Zoom application and unsynchronized method through the WhatsApp application was carried out for two weeks involving 85 elementary, junior, and high school teachers from various regions of Bali province. Evaluation of this program is measured through few indicators: (1) success in identifying problems and themes for action research, (2) success in formulating solutions to overcome problems, (3) success in drafting action research proposals, and (4) success in compiling a draft of action research articles. The evaluation results showed that (1) 90% of participants succeeded in compiling problem identification and research themes, 80% of participants succeeded in formulating solutions to overcome problems, (3) 80% of participants succeeded in compiling a draft proposal, and (4) 65% of participants have successfully drafted a scientific articles from their action research studies. This results indicate that online training and mentoring was quite successful in increasing teacher motivation and ability to compile action research and scientific articles.